Personality resemblance between parents and offspring: study of five factors across four samples and questionnaires - Vukasović, Tena; Butković, Ana; Keresteš, Gordana; Brković, Irma; Bratko, Denis (2011)
It is well know that personality is substantially heritable, but it is also known that heritability estimates may vary depending on some methodological variables, such as study design. Family study design, which has a limitation of not being able to separate genetic and environmental influences, can provide evidence of familial aggregation of personality. The aim of this study was to compare four different Croatian samples using the same family design, but different five‐factor personality questionnaires (BFI, NEO‐FFI, FFPI, IPIP). Father‐offspring correlations, mother‐offspring correlations and regressions of offspring on midparent score were computed for the five broad personality domains in each sample. Father‐offspring correlations ranged between 0.04 and 0.34 for different questionnaires, while mother‐offspring correlations ranged between 0.08 and 0.28. Regressions of offspring on midparent scores ranged between 0.05 and 0.35. These results are congruent with earlier findings of lower familial aggregation of personality compared to heritability estimates from studies using twin design. Differences in familial aggregation across four samples and questionnaires are discussed.
Knjiga sažetaka nije tiskana, već je dostupna isključivo na službenoj internetskoj stranici: http://www.issid2011.com/program/posters.pdf
Projekt MZOS
Projekt MZOS
ENG